Studi Variasi Pelarut Terhadap Efek Antioksidan Pada Ekstrak Daun Bidara ( Ziziphus Jujube Mill ) Menggunakan Metode Peredaman Radikal Bebas 1,1-Difenil-2-Pikrilhidrazil (DPPH) - Yusman, Dayandi; Risda, Waris; Ahmad, Najib (PHARMACY UMI JOURNAL SYSTEM, 2023)
Study On a Solvent Variation againtst the Antioxidant Effect on Red Date leaf Extract (Ziziphus Jujuba mill). by free Radical Scavanging 1,1-dipheyil-2-picrilhidrazil (DPPH). (Supervised by Ahmad Najib and Risda Waris) The research aimed to determine the differences of the antioxidant activities by three types of the extract variantions (Ziziphus Jujuba mill.) against DPPH (free radicals). Red date leaf extract was extracted by sequence maceration method by N-Hexane, ethyle acetal, and ethanol. The extract obtained was analyzed its antioxidant activity againts DPPH free radicals. The tests were conducted in 5 series concentration (20, 40, 60, 80 and 100) ppm using methanol. The activity on the free radicals, the absorbances were measured by a spectrophotometer at the maimum wavelength of 515 nm and calculated IC50 value. The results showed that n-hexane, ethyl acetate, and ethanol extract on the red date leaves had the activities with IC50 value with the very weak intensity as antioxidants ( >200 ppm)